Is it possible to discontinue glucocorticoids in rheumatoid arthritis with the use of synthetic disease-modifying antirheumatic drugs? - O. B. Iaremenko; H. M. Mykytenko (Zaporožskij Medicinskij Žurnal)
The aim of the work is to study the possibility of glucocorticoid (GC) discontinuation or their target dose achievement in patients (pts) with rheumatoid arthritis (RA) receiving conventional synthetic disease-modifying antirheumatic drugs (DMARDs).